2020
DOI: 10.26508/lsa.202000660
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming of fibro/adipogenic progenitors facilitates muscle regeneration

Abstract: In Duchenne muscular dystrophy (DMD), the absence of the dystrophin protein causes a variety of poorly understood secondary effects. Notably, muscle fibers of dystrophic individuals are characterized by mitochondrial dysfunctions, as revealed by a reduced ATP production rate and by defective oxidative phosphorylation. Here, we show that in a mouse model of DMD (mdx), fibro/adipogenic progenitors (FAPs) are characterized by a dysfunctional mitochondrial metabolism which correlates with increased adipogenic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 79 publications
3
56
0
Order By: Relevance
“…Further, HDAC inhibitors blocked adipogenic differentiation of FAPs and improved their ability to promote differentiation of MuSCs, through upregulation of the soluble factor follistatin in early stage, but not late stage, mdx mice; which are also characterized by metabolic defects (Mozzetta et al, 2013). Using the same mdx mouse model of muscular dystrophy, Reggio et al (2019) demonstrated that follistatin is diminished in FAPs due to reduced β-catenin signaling. However, short-term high fat diet feeding reversed this defect by increasing β-catenin levels which promoted IGF-1 and follistatin expression and release leading to improved ability of FAPs to support myogenesis and muscle regeneration (Reggio et al, 2019).…”
Section: The Relationship Between Metabolic Stress and The Fap Secretomementioning
confidence: 99%
See 4 more Smart Citations
“…Further, HDAC inhibitors blocked adipogenic differentiation of FAPs and improved their ability to promote differentiation of MuSCs, through upregulation of the soluble factor follistatin in early stage, but not late stage, mdx mice; which are also characterized by metabolic defects (Mozzetta et al, 2013). Using the same mdx mouse model of muscular dystrophy, Reggio et al (2019) demonstrated that follistatin is diminished in FAPs due to reduced β-catenin signaling. However, short-term high fat diet feeding reversed this defect by increasing β-catenin levels which promoted IGF-1 and follistatin expression and release leading to improved ability of FAPs to support myogenesis and muscle regeneration (Reggio et al, 2019).…”
Section: The Relationship Between Metabolic Stress and The Fap Secretomementioning
confidence: 99%
“…In contrast, fibrogenesis and chondrogenesis seems to require utilization of glycolysis during differentiation (Shyh-Chang et al, 2013;Zhao et al, 2019). FAPs from regenerating mdx muscle have an increase in glycolytic proteins and a reduction of mitochondrial proteins compared to control mice (Marinkovic et al, 2019) resulting in mdx FAPs favoring glycolysis over oxidative metabolism (Reggio et al, 2019). Interestingly, these metabolic changes were associated with greater proliferative capacity and adipogenic potential in vitro which was reversed by inhibiting glycolysis and forcing oxidative metabolism (Reggio et al, 2019).…”
Section: Fibro/adipogenic Progenitors As the Cellular Source Of Intermentioning
confidence: 99%
See 3 more Smart Citations